Reproductive Biology and Sexual Dimorphism in Bokermannohyla alvarengai (Anura: Hylidae) - Centeno, Fernanda C. [UNESP]; Vivancos, Aurélien; Andrade, Denis V. [UNESP] (Herpetologists League, 2021)
The general pattern of sexual size dimorphism (SSD) in amphibians is characterized by females being larger than males. However, the reverse pattern, a male-biased SSD, may be widespread within some particular groups, as seems to be the case for the Neotropical treefrog genus Bokermannohyla. Although SSD is commonly associated with factors influential to breeding success, the evolutionary determinants of SSD remain controversial. Thus, the study of SSD, particularly on lesser-known species, remains critical to advance our understanding of the evolution of body size and other traits associated with the reproductive biology of amphibians. Herein, we examined the occurrence of sexual dimorphism in body size and other morphometric attributes in Bokermannohyla alvarengai and provided a detailed account of its reproductive biology. This species is endemic to a threatened habitat, occurs at low densities, and has a poorly documented natural history. We found that, at maturity, males of B. alvarengai were larger than females, with hypertrophied forelimbs and larger prepollex spines. This set of features, common to other Bokermannohyla species, is often attributed to the occurrence of male territorial defense and aggression between males. We found that B. alvarengai has a prolonged breeding season that extends from the middle of the dry season to the middle of the rainy season. Adult males did not form breeding aggregations and seemed to establish and defend territories; these males often had skin scars indicative of male-male combat. However, alternative interpretations for differences in body size and secondary sexual characters cannot be ruled out and are discussed.
Keywords: Breeding; Male-male combat; Morphometry; Reproduction; Treefrog